2021
DOI: 10.3389/fimmu.2021.744396
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Ocular Manifestations in Autoimmune Disease

Abstract: The global prevalence of autoimmune diseases is increasing. As a result, ocular complications, ranging from minor symptoms to sight-threatening scenarios, associated with autoimmune diseases have also risen. These ocular manifestations can result from the disease itself or treatments used to combat the primary autoimmune disease. This review provides detailed insights into the epidemiological factors affecting the increasing prevalence of ocular complications associated with several autoimmune disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 209 publications
(221 reference statements)
0
27
0
1
Order By: Relevance
“…A unifying role of the oxidative stress between cataracts and rheumatoid arthritis has also been suggested [ 26 ]. The body’s immune system attacking self-antigens also plays a crucial role in arthritis and ocular comorbidities [ 27 ]. Corticosteroid could also be a linkage between these two comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…A unifying role of the oxidative stress between cataracts and rheumatoid arthritis has also been suggested [ 26 ]. The body’s immune system attacking self-antigens also plays a crucial role in arthritis and ocular comorbidities [ 27 ]. Corticosteroid could also be a linkage between these two comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have demonstrated that this eye condition is frequently disrupted in diverse ocular pathologies in which several immunological components are implicated in the etiopathology of these ocular diseases [ 21 ]. In this sense, the immune system has been involved directly or indirectly in a wide range of ocular pathologies of the anterior and posterior chambers of the eye [ 22 ]. Dry eye syndromes, autoimmune uveitis, age-related macular degeneration (AMD), glaucoma, and autoimmune retinopathy are some of the anterior and posterior segment diseases in which the immune system plays a main role in their pathological development [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dry eye syndromes, autoimmune uveitis, age-related macular degeneration (AMD), glaucoma, and autoimmune retinopathy are some of the anterior and posterior segment diseases in which the immune system plays a main role in their pathological development [ 21 ]. Some autoimmune diseases such as rheumatoid arthritis, systemic lupus erythematosus, Sjögren’s syndrome, and graft-versus-host disease are involved in the development of several ocular pathologies mentioned above [ 22 , 23 ]. Although CD4+ T cells have been described in the last two decades as the main actors in the pathogenesis of ocular autoimmune diseases, several studies have demonstrated that B cells and the autoantibodies produced by them also have an outstanding role in the immunopathogenic process of these diseases [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bu sebeple, göz muayenesi ortaya çıkan oküler semptomları zamanında teşhis etmek, araştırmak ve tedavi etmek için hastalık yönetiminin rutin bir parçası haline gelmelidir. [3] Tablo 1. Sistemik…”
Section: Introductionunclassified